Implementation of the Theory of Legal Norm Hierarchy in the Muhammadiyah Tarjih Manhaj in the Study of Thematic Hadith on Social Justice: A Case Study of Responding to Non-Muslim Greetings - Rachmawan, Hatib (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This study examines the application of the Theory of the Hierarchy of Islamic Legal Norms within the Manhaj Tarjih of Muhammadiyah as an epistemological framework for thematic studies of hadiths related to social justice. Focusing on a case study of the Muhammadiyah Tarjih Council's fatwa regarding responses to greetings from non-Muslims, the research aims to critically reassess the normative foundation and sociocultural context of the fatwa through a hierarchical approach to Islamic legal norms. Utilizing a qualitative library-based method and thematic analysis, the study engages with a range of relevant primary and secondary sources. The findings suggest that the hierarchical model offers a more flexible and contextually grounded interpretation of the hadith, especially when core Islamic values, such as justice (al-ʿadl), public welfare (al-maṣlaḥah), and social harmony, are prioritized. The study recommends a more contextual, inclusive, and dialogical fatwa methodology to enhance social cohesion in multicultural societies and to align Islamic legal thought with contemporary ethical imperatives.